The Role of Trust in Mediating the Influence of Service Quality and Customer Satisfaction on Customer Loyalty in the Money Changer Industry Badung Regency - DEWI, Anak Agung Ayu Rai Sukma; INDIANI, Ni Luh Putu; WAHYUNI, Ni Made (PT Keberlanjutan Strategis Indonesia, 2024)
Currently, competition in the business world feels increasingly fierce, this can also be felt in Indonesia. Likewise, the conditions that occur in foreign currency exchange service businesses or what are usually called Money Changers. In Bali, especially in the Badung area, the level of business competition is increasing along with the increasing number of companies operating in similar fields. According to data from the Foreign Exchange Traders Association (APVA), the number of money changers in Badung Regency has reached 117 companies. phenomenon that occurs in the money changer industry in Badung Regency, which still does not have a company license, which causes the money changer to sell prices at foreign exchange rates that do not comply with the policies of KUPVA BB (Non-Bank Foreign Currency Exchange Business Activities) such as giving commissions to customers, thereby making The customer feels disadvantaged because the amount exchanged does not match the amount received. This research aims to analyze the influence of the role of trust in mediating the influence of customer satisfaction on customer loyalty. The population of this research is all tourists visiting Badung Regency. The sample used was 120 foreign tourists in Badung Regency. The data collection method uses a survey method and the research instrument uses a questionnaire. The analysis technique used to answer the hypothesis is inferential analysis using Partial Least Square (PLS). The research results found that service quality has a positive and significant effect on customer loyalty. Service quality has a positive and significant effect on trust.